2021
DOI: 10.1017/s0950268821000091
|View full text |Cite
|
Sign up to set email alerts
|

How to improve infectious disease prediction by integrating environmental data: an application of a novel ensemble analysis strategy to predict HFMD

Abstract: This study proposed a novel ensemble analysis strategy to improve hand, foot and mouth disease (HFMD) prediction by integrating environmental data. The approach began by establishing a vector autoregressive model (VAR). Then, a dynamic Bayesian networks (DBN) model was used for variable selection of environmental factors. Finally, a VAR model with constraints (CVAR) was established for predicting the incidence of HFMD in Chengdu city from 2011 to 2017. DBN showed that temperature was related to HFMD at lags 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Since it has been already reported that the forecasting performance of the VARMA model was superior to that of the univariate time series model ( 27 ), this study chose another two mainstream methods, SEIRS and LSTM, as comparison models. The two methods respectively represented the mechanism models and machine learning methods, which could serve as benchmarks for forecasting performance comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Since it has been already reported that the forecasting performance of the VARMA model was superior to that of the univariate time series model ( 27 ), this study chose another two mainstream methods, SEIRS and LSTM, as comparison models. The two methods respectively represented the mechanism models and machine learning methods, which could serve as benchmarks for forecasting performance comparison.…”
Section: Methodsmentioning
confidence: 99%